(untitled) (Research, Society and Development, 2021)
In Brazil, the right to health is enshrined in the Federal Constitution of 1988 as a fundamental social right, and therefore, receives full legal protection, and it was with the creation of the Sistema Único de Saúde (SUS) that the debate on the financing of health policy intensified by managers and entities, considering the structure insufficient to meet the demand of Brazilian citizens. Thus, this article aims to analyze public health in Brazil from a historical-critical perspective, based on the Constitutional Charter 1988, Law n° 8080 and EC/95, which regulate the actions and budget of the SUS. if in observing how these laws are applied nowadays and if they manage to supply the population’s needs and demands. To carry out the research, the deductive approach method was used, starting from the analysis of the constitutional law, for its practical application in the context of the pandemic. A historical-evolutionary analysis was carried out. The level of depth of this study was built through an exploratory research, the data were collected through bibliographical and documentary research. In view of the reflections studied throughout the research, it was possible to see that, despite the fundamental rights being consolidated in the Magna Carta, it appears that the State as guarantor of fundamental rights does not guarantee enough to fully implement these guarantees generated mainly by the insufficient application of resources and by the lack of adequate system service during the crisis aggravated by the pandemic in Brazil.